Gender-Based Violence and Violence Against Children : Prevention and Response Services in Uganda’s Refugee-Hosting Districts - World Bank (World Bank, Washington, DC, 2020)
Uganda currently hosts the third-largest refugee population in the world, and the largest in Africa. In May 2020, the country was hosting about 1.4 million refugees and asylum seekers, mostly in the West Nile, Northern, and Western parts of the country. The majority of these refugees are from South Sudan and the Democratic Republic of Congo. Women and children comprise 82 percent of Uganda’s overall refugee population, about 56"percent of refugees are below the age of 15, and 25 percent are younger than five years of age (World Bank 2019). Gender-based violence (GBV) and violence against children (VAC) are key protection concerns for refugees and host communities alike, with women and girls disproportionately affected. The United Nations High Commissioner for Refugees (UNHCR) recorded 4,297 cases of GBV in refugee settlements between January and November 2019. In addition, the 2016 Uganda Demographic and Health Survey reveals a high prevalence of GBV in districts that host refugees. The Development Response to Displacement Impacts Project (DRDIP) is a World Bank-funded project that seeks to address the impacts of forced displacement in communities hosting refugees in 11 districts in Uganda. DRDIP provides access to basic social services, expands economic opportunities, and enhances environmental management targeted at both refugees and host communities. DRDIP conducted a rapid assessment in 11 of the 12 refugee hosting districts to: (1) identify key risk factors for GBV and VAC and to examine the intersections between them, with an emphasis on host communities; (2) map existing GBV and VAC prevention and response services in both refugee and host communities, including the effectiveness of existing referral pathways; and (3) provide recommendations to align and link the GBV and VAC prevention and response services provided in refugee settlements and host communities. The contributions of this assessment will strengthen GBV and VAC risk management associated with the implementation of DRDIP. Data for this assessment were collected before the COVID-19 outbreak, but subsequent data show an increase in GBV and VAC, exacerbated by confinement measures, particularly adolescents girls and women at risk of intimate partner violence. This assessment complements the UNHCR-led interagency assessment that focused on GBV and VAC in 11 refugee settlements (UNHCR and OPM 2019). The DRDIP analysis includes a comprehensive mapping of services for GBV and VAC prevention and response across the key sectors of health, police, justice, and social services in refugee settlements and host communities. In addition, qualitative data were collected through focus group discussions with refugees and local populations; interviews with key informants, including duty bearers such as health workers and police officers; and consultations with local stakeholders.